1993
DOI: 10.1091/mbc.4.12.1267
|View full text |Cite
|
Sign up to set email alerts
|

Wnt family proteins are secreted and associated with the cell surface.

Abstract: Members of the Wnt gene family are proposed to function in both normal development and differentiation as well as in mammary tumorigenesis. To understand the function of Wnt proteins in these two processes, we present here a biochemical characterization of seven Wnt family members. For these studies, AtT-20 cells, a neuroendocrine cell line previously shown to efficiently process and secrete Wnt-1, was transfected with expression vectors encoding Wnt family members. All of the newly characterized Wnt proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 33 publications
7
108
0
Order By: Relevance
“…Signaling through some Wnts such as; Wnt1 (Hinck et al, 1994;Young et al, 1998;Shimizu et al, 1997), Wnt3a (Shimizu et al, 1997) and Wnt8 (Wikramanayake et al, 2004;Kohn and Moon, 2005) has been shown to correlate with accumulation of β-catenin in the nucleus and transcriptional changes, while signaling trough others like Wnt5a (Shimizu et al, 1997;Kikuchi et al, 2012) and Wnt11 (Kohn and Moon, 2005;Tada and Smith, 2000;Pandur et al, 2002) is β-catenin-independent and involves regulation of cytoskeleton or calcium release. All the metazoan species express Wnt genes and all of those genes encode secreted proteins based on their amino acid structure and biochemical characterization (Coudreuse and Korswagen, 2007;Smolich et al, 1993). Upon translation and targeting to the extracellular space, Wnt proteins are exposed to various modifications, which are essential for folding, secretion and Wnt-signaling activity (Mikels and Nusse, 2006;Coudreuse and Korswagen, 2007;Willert and Nusse, 2012).…”
Section: Wnt Signaling Pathwaysmentioning
confidence: 99%
“…Signaling through some Wnts such as; Wnt1 (Hinck et al, 1994;Young et al, 1998;Shimizu et al, 1997), Wnt3a (Shimizu et al, 1997) and Wnt8 (Wikramanayake et al, 2004;Kohn and Moon, 2005) has been shown to correlate with accumulation of β-catenin in the nucleus and transcriptional changes, while signaling trough others like Wnt5a (Shimizu et al, 1997;Kikuchi et al, 2012) and Wnt11 (Kohn and Moon, 2005;Tada and Smith, 2000;Pandur et al, 2002) is β-catenin-independent and involves regulation of cytoskeleton or calcium release. All the metazoan species express Wnt genes and all of those genes encode secreted proteins based on their amino acid structure and biochemical characterization (Coudreuse and Korswagen, 2007;Smolich et al, 1993). Upon translation and targeting to the extracellular space, Wnt proteins are exposed to various modifications, which are essential for folding, secretion and Wnt-signaling activity (Mikels and Nusse, 2006;Coudreuse and Korswagen, 2007;Willert and Nusse, 2012).…”
Section: Wnt Signaling Pathwaysmentioning
confidence: 99%
“…Cadigan and M. Peifer transported through the endomembrane system to the cell surface and undergo several modifications. Wnts undergo N-linked glycosylation (Burrus and McMahon 1995;Kadowaki et al 1996;Komekado et al 2007;Kurayoshi et al 2007;Mason et al 1992;Smolich et al 1993;Tanaka et al 2002). Several Wnts also are palmitoylated at the first conserved cysteine (Galli et al 2007;Kadowaki et al 1996;Komekado et al 2007;Willert et al 2003).…”
Section: Preparing For Departure-posttranslational Wnt Modificationsmentioning
confidence: 99%
“…A series of experiments using tunicamycin have shown that Wnt-5a is modified with asparagine-linked glycans [29]. However, which amino acids are modified has not been determined.…”
Section: Glycosylation Of Wnt-5amentioning
confidence: 99%